1998
DOI: 10.1038/bjc.1998.337
|View full text |Cite
|
Sign up to set email alerts
|

Past exposure to hepatitis B virus as a risk factor for hepatocellular carcinoma in patients with chronic liver disease

Abstract: Summary The aim of the study was to determine whether past exposure to hepatitis B virus (HBV) influences the risk of the development of hepatocellular carcinoma (HCC) in Japanese patients with chronic liver disease (CLD). We conducted a hospital-based case-control study of 141 HCC patients with CLD and 151 controls with CLD but without HCC. Past exposure to HBV was assessed by antibody to hepatitis B core antigen (anti-HBc) positivity. Ninety-two patients (65%) with HCC were anti-HBc positive compared with 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
(19 reference statements)
2
31
0
Order By: Relevance
“…In the absence of immunosuppression, the possibility of reactivation of HBV infection and progressive development of cirrhosis should be minimal. In a case-control study, 18 past exposure to HBV infection has been shown to increase the risk for the development of hepatocellular carcinoma by twofold in Japanese patients with chronic liver disease, but the odds ratio was not significant when anti-HBs was positive, as well. In patients with a biochemically and histologically normal liver, anti-HBc positivity alone has not been shown to be an independent risk factor for hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of immunosuppression, the possibility of reactivation of HBV infection and progressive development of cirrhosis should be minimal. In a case-control study, 18 past exposure to HBV infection has been shown to increase the risk for the development of hepatocellular carcinoma by twofold in Japanese patients with chronic liver disease, but the odds ratio was not significant when anti-HBs was positive, as well. In patients with a biochemically and histologically normal liver, anti-HBc positivity alone has not been shown to be an independent risk factor for hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, occult HBV infection is associated with anti-HBc with or without anti-HBs, and serum antiHBc and anti-HBs are considered markers of past HBV infection that may also serve as useful markers for HCC risk factors [51][52][53] . However, no anti-HBs or anti-HBc can be detected in a significant proportion of patients with occult B infection [54] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that anti-HBc positivity was associated with the development of HCC in patients with HCV-associated chronic liver disease (11,(24)(25)(26). However, considering the natural history of all HCV infections, the results of those previous studies have some problems, i.e., the observation period was short and the research was performed in a retrospective manner in patients with chronic hepatitis and liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…That is, anti-HBc, which was initially considered to be an index for the past HBV infection in which all HBV had been cleared, has emerged as a convincing marker of occult hepatitis B (19,(21)(22)(23). Also, several studies showed that the anti-HBc positivity was associated with the development of HCC in patients with HCV-associated chronic liver disease (11,(24)(25)(26), but these associations have not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%